The Nurses' Role in the Cardiac Rehabilitation Team : Data from the Perfect-CR Study - Lidin, Matthias; Michelsen, Halldora Ögmundsdottir ; 0000-0002-8900-7916; Hag, Emma; Stomby, Andreas; Schlyter, Mona; Bäck, Maria; Hagström, Emil; Leosdottir, Margret (Journal of Cardiovascular Nursing, 2025)
Background Nurses constitute a central profession in the cardiac rehabilitation (CR) team delivering comprehensive CR to individuals with cardiovascular disease. We aimed to identify specific components reflecting the nurses' role in the CR team associated with attainment of risk factor targets post myocardial infarction. Methods Center-level data (n = 78) was used from the Perfect-CR study, in which structure and processes applied at CR centers in Sweden (including details on the nurses' role) were surveyed. Patient-level data (n = 6755) was retrieved from the SWEDEHEART registry. Associations between structure/processes and target achievement for systolic blood pressure (BP) (<140 mm Hg) and low-density lipoprotein cholesterol (LDL-C, <1.8 mmol/L) at 1 year post myocardial infarction were assessed using logistic regression. Results Structure and processes reflecting nurses' autonomy and role in the CR team associated with patients achieving systolic BP and/or LDL-C targets included the following: nurses having treatment algorithms to adjust BP medication (odds ratio [95% confidence interval]: systolic BP, 1.22 [1.05-1.42]; LDL-C, 1.17 [1.03-1.34]) and lipid-lowering medication (systolic BP, 1.14 [1.00-1.29]; LDL-C, 1.17 [1.05-1.30]), patients having the same nurse throughout follow-up (systolic BP, 1.07 [1.03-1.11]; LDL-C, 1.10 [1.06-1.14]), number of follow-up hours with a nurse (systolic BP, 1.13 [1.07-1.19]), having regular case rounds to discuss patient cases during follow-up (LDL-C, 1.22 [1.09-1.35]), and nurses having training in counseling methods (systolic BP, 1.06 [1.03-1.10]). Conclusion Components reflecting CR nurses' autonomy and role in the team are of importance for patients attaining risk factor targets post myocardial infarction. The results could provide guidance for optimizing nurses' competence and responsibilities within the CR team to improve patient care.
Publisher Copyright: © Wolters Kluwer Health, Inc. All rights reserved.
Keywords: cardiac rehabilitation; data registry; myocardial infarction; nurses; risk factors; secondary prevention